Mood Enhancement as a Legitimate Goal of Medicine: Rethinking the Treatment-Enhancement Dichotomy in the Context of Human Wellbeing - Verwey, Hanneke (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPhil)--Stellenbosch University, 2020.